2024
DOI: 10.1038/s41413-023-00306-4
|View full text |Cite|
|
Sign up to set email alerts
|

Insights and implications of sexual dimorphism in osteoporosis

Yuan-Yuan Zhang,
Na Xie,
Xiao-Dong Sun
et al.

Abstract: Osteoporosis, a metabolic bone disease characterized by low bone mineral density and deterioration of bone microarchitecture, has led to a high risk of fatal osteoporotic fractures worldwide. Accumulating evidence has revealed that sexual dimorphism is a notable feature of osteoporosis, with sex-specific differences in epidemiology and pathogenesis. Specifically, females are more susceptible than males to osteoporosis, while males are more prone to disability or death from the disease. To date, sex chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 520 publications
0
4
0
Order By: Relevance
“…On the other hand, secondary osteoporosis, which is associated with pharmacological agents, including glucocorticoids (cortisone, prednisone, dexamethasone, and hydrocortisone), or underlying comorbidities like diabetes type 1 (lower bone strength), types 2 (increased bone cortical porosity), and other dysmetabolic conditions (the so-called "diabetic osteoporosis"), is more prevalent in men. Also, men have a higher risk of mortality following (either primary or secondary) osteoporotic fractures than women [42], as shown in the following section.…”
Section: Sex-and Gender-specific Physiopathology Of Bone Lossmentioning
confidence: 86%
“…On the other hand, secondary osteoporosis, which is associated with pharmacological agents, including glucocorticoids (cortisone, prednisone, dexamethasone, and hydrocortisone), or underlying comorbidities like diabetes type 1 (lower bone strength), types 2 (increased bone cortical porosity), and other dysmetabolic conditions (the so-called "diabetic osteoporosis"), is more prevalent in men. Also, men have a higher risk of mortality following (either primary or secondary) osteoporotic fractures than women [42], as shown in the following section.…”
Section: Sex-and Gender-specific Physiopathology Of Bone Lossmentioning
confidence: 86%
“…Among these, CDH-13 was found to inhibit osteoclast differentiation and delay age-related bone loss in aged mice, suggesting its potential therapeutic role in preventing osteopenia [120]. Another study illustrated, through proteomic analysis, that estrogen promotes autophagy in human osteoblasts during differentiation to promote survival and mineralization by upregulating RAB3 GTPase-activating protein [135,136]. Furthermore, through proteomic techniques and functional validation, ubiquitin C-terminal hydrolase 1 (UCHL1) was shown to stabilize the transcriptional coactivator with PDZbinding motif (TAZ) by deubiquitination, inhibiting osteoclast formation.…”
Section: Proteomic Identification Of Novel Therapeutic Targetsmentioning
confidence: 99%
“…Following publication of the original article, 1 the authors reported an error in figure 1. During re-reading our previously published article entitled “Insights and implications of sexual dimorphism in osteoporosis” 1 in Bone Research, we regrettably found that the terms of “hematopoietic precursors” and “mesenchymal precursors” in Figure 1b were wrongly reversed, which have been corrected below.…”
mentioning
confidence: 99%
“…Following publication of the original article, 1 the authors reported an error in figure 1. During re-reading our previously published article entitled “Insights and implications of sexual dimorphism in osteoporosis” 1 in Bone Research, we regrettably found that the terms of “hematopoietic precursors” and “mesenchymal precursors” in Figure 1b were wrongly reversed, which have been corrected below. Although those modifications do not affect the results and conclusion in the article, all the authors agree to correct this negligence by providing corrected Figure 1, to guarantee the accuracy of the article.…”
mentioning
confidence: 99%